Warm Vinegar Fomentation And Conventional Method In Lowering The Body Temperature Among Oregano Phosphorous Poisoning Patients - Jadhav, G uruprasad P; Gholap, Manisha C; Patange, Aparna P.; Shinde, Mahadeo B (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Organophosphorous poisoning(OPP) is a major community health problem and one of the main problems in the emergency department. Objective: Study investigated the effectiveness of Warm vinegar fomentation and conventional method in lowering the body temperature among oregano phosphorous poisoning patient. Methods: Post-test only control group design was used to conduct the study among organo phosphorous patients totally 40 organo phosphorous patients were selected by Purposive sampling technique. Ethical permission was obtained before the data collection. Intensive care Unit at tertiary care hospital, Karad. Warm vinegar fomentation and conventional method provided to the OPP patients in the experimental group and control group respectively. Data was collected by using a structured questionnaire. Results: Significant difference found between the warm vinegar fomentation and conventional method at the level of p